Organizational and economic aspects of triplet therapy of relapsed/refractory multiple myeloma in the Russian healthcare setting - E. A. Pyadushkina; E. V. Derkach; V. I. Ignatyeva; E. E. Yagnenkova; T. Yu. Klitochenko; T. V. Shelekhova; A. N. Levanov (IRBIS LLC, 2021)
Background. The introduction of innovative drugs has significantly increased the treatment effectiveness in patients with relapsed/refractory multiple myeloma (RRMM), but the question of whether these expensive options can be financially secured remains open.Objective: to assess the cost of triplets of targeted drugs ixazomib, carfilzomib, elotuzumab and daratumumab with lenalidomide and dexamethasone used in the treatment of RRMM, and to determine possible payment options for this therapy at the level of the Russian Federation subjects.Material and methods. The cost of an annual course of treatment with the studied regimens with centralized purchases and the cost of targeted drugs per hospitalization case were calculated based on the maximum registered prices, recommended doses and treatment regimens. The normative legal acts regulating the payment of drug therapy for multiple myeloma were analyzed and possible financing channels and their limitations were identified. Using the example of the Volgograd and Saratov Regions, tariffs under the compulsory medical insurance system were calculated and their sufficiency in covering the cost of targeted therapy was estimated.Results. The cost of an annual course of triplet therapy per patient in the case of centralized procurement of drugs ranged from 5.51 million rubles (regimen with ixazomib) up to 8.03 million rubles (regimen with carfilzomib). The cost per hospitalization, depending on the number of doses, ranged from 80,667-242,000 rubles (ixazomib, 1-3 doses) in the Saratov Region up to 239,618-958,472 rubles (daratumumab, 1-4 doses) in the Volgograd Region. Possible reimbursement channels are High-Cost Nosologies (HCN), Obligatory Medical Insurance (OMI) and Regional Drug Coverage (RDC) programs, nevertheless triplet therapy cannot be purchased via the single channel and the combination of them is required. It has been shown that, in most cases, the costs for a case of targeted drug treatment in studied regions are covered by the average tariff for the corresponding diagnosis-related group (DRG), except for cases with a maximum duration in a day hospital setting. An analysis of the RDC lists and the procurement of drugs in the studied regimens at the expense of regional budgets showed that lenalidomide, ixazomib, carfilzomib, elotuzumab and daratumumab are included in the restrictive list in regions 77, 74, 66, 63 and 47, but they are purchased only in regions 15, 24, 6, 4 and 6, respectively.Conclusion. The use of a triplet with ixazomib is characterized by the lowest costs, which indicates its greater economic attractiveness relative to carfilzomib, daratumumab and elotuzumab in the treatment of patients with RRMM. The tariffs established in the current DRG model retain the possibility of paying for treatment with the high-cost medicines at the expense of the OMI funds in combination with the HCN or RDC programs. There are reasons to believe that the expansion of the list of 14 HCN program will increase the provision of patients with highly effective therapy and also reduce the financial burden on the regions.